PENGARUH DANA PIHAK KETIGA DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN BANK UMUM BUMN YANG TERDAFTAR DI BEI PERIODE 2017-2022 - Dewi, Rosmala; Priharti, Rr. Dimas Veronica; Jelita, Jelita (KOLEGIAL, 2024)
This research discussed the influence of third party funds and liquidity on profitability instate-owned commercial banking companies listed on the Indonesian Stock Exchange (BEI)for the 2017-2022 period. The analytical method used in this research was Multiple LinearRegression. Apart from that, this research also carried out classical assumption tests whichincluded normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelationtests. The results of this research showed that partially Third Party Funds (DPK) did nothave a significant influence on profitability with a significance value of 0.155 > 0.05.Meanwhile, liquidity had a significant negative influence on profitability with a significancevalue of 0.021 < 0.05. The results of this research showed that Third Party Funds (DPK) andLiquidity (LDR) simultaneously or together had a significant influence on Profitability (ROA)with a significance value of 0.035 < 0.05. The results of the R Square DeterminationCoefficient Analysis were 0.273 or 27.3, this showed that the contribution percentage of theinfluence of Third Party Funds (X1) and Liquidity (X2) on the rise and fall of Profitability (Y)was 27.3% while the remaining 72.7% was due to by other factors not researched or used inthis research